Resiliensi akademik pada mahasiswa perantau: Bagaimana peranan dukungan sosial teman sebaya? - Ma’ruf Nur Abdillah; Suroso; Isrida Yul Arifiana (INNER: Journal of Psychological Research, 2023)
Abstract Academic resilience is the ability of individuals to adapt to overcome challenges, difficulties, and pressures in academic settings. Academic resilience needs to be owned by every student in facing lectures. One of the factors that can affect academic resilience is peer social support. The purpose of this study was to analyze the relationship between peer social support and academic resilience in overseas students. This research is a correlational quantitative research type. The population used overseas students at the University of 17 August 1945 Surabaya with a total of 15427 students. The sample obtained was 120 using the Accidental Sampling technique. The data collection instrument used a Likert scale. Data analysis using the Product Moment correlation technique. Results of data analysis that have been carried out show a significant positive relationship between peer social support and academic resilience in overseas students. It is recommended for future researchers to add variables and develop research locations. Keywords: academic resilience, peer social support, overseas students